Industrial policy, employment policy and the non-traded sector - O'Rourke, Kevin (Statistical and Social Inquiry Society of Ireland, 1995)
This paper will critically examine the assumptions on which their [Irish policy makers] policies have been based, and suggest a more constructive role for government intervention. There are three quite distinct sections. The first section will outline the traditional theoretical basis for Irish government policy, and ask whether it makes sense. The second section argues that the non-traded sector is the key to a country's competitiveness. The third section will investigate the effects on the Irish economy of opening up sectors, hitherto nontraded (due to government restrictions), to foreign competition. In particular, the employment effects of such a move are examined, using a computable general equilibrium model developed by the author, in collaboration with Kevin Denny and Aoife Hannan of UCD.
Barrington Lecture 1994/1995
Read before the Society, 24 November 1994 - This lecture is delivered under the auspices of the Barrington Trust (founded by the bequest of John Barrington, Esq.) with the collaboration of the Journal of the Statistical and Social Inquiry Society of Ireland.
Keywords: Non-traded sector; Employment policy; 314.15